2016
DOI: 10.1002/ijc.29962
|View full text |Cite
|
Sign up to set email alerts
|

CD56-positive lymphocyte infiltration in relation to human papillomavirus association and prognostic significance in oropharyngeal squamous cell carcinoma

Abstract: Human papillomavirus (HPV)-related squamous cell carcinoma of the oropharynx (OSCC) are clinical and biological distinct from their HPV-unrelated counterparts. Patients with HPV-related OSCC display improved prognosis and therefore we investigated possible immune cell infiltrations associated with this tumor phenotype. We retrospectively analyzed a randomly selected cohort of 140 OSCC for presence of immune cells and HPV by immunohistochemistry and PCR followed by beadbased hybridization (Luminex technology). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 47 publications
5
72
0
4
Order By: Relevance
“…The success of an immune checkpoint inhibitor blockade is dependent on anti-tumor-specific effector cells [48, 49]. Similar to a patient with colon cancer [21, 45, 50], the stimulation with TKD/IL-2 induced a shift towards the CD3 − /CD56 bright NK cell subset which was further propagated by nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…The success of an immune checkpoint inhibitor blockade is dependent on anti-tumor-specific effector cells [48, 49]. Similar to a patient with colon cancer [21, 45, 50], the stimulation with TKD/IL-2 induced a shift towards the CD3 − /CD56 bright NK cell subset which was further propagated by nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor infiltration of NK cells is associated with a better prognosis in several cancer entities, such as colorectal cancer, non-small cell lung cancer, and clear cell renal cell carcinoma (7882). For HNSCC, several studies showed a positive correlation of high NK cell infiltration, especially in HPV + HNSCC, in primary tumors, and overall survival rates (8385). Thus, low numbers of infiltrated NK cells might be one explanation for insufficient HNSCC immunosurveillance, and these patients might benefit from sNKG2DL depletion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, deletion (14%) or mutation (8%) of tumor necrosis factor receptor-associated factor 3 (TRAF3, encoded on 14q32.32), involved in the innate and acquired antiviral immune response, is overrepresented in HPV-related HNSCC [24]. Innate immunity appears to be significant for HPV-related HNSCC, since genes coding for HLA I components are frequently mutated and higher numbers of CD56-positive natural killer cells have been reported for HPV-related OPSCC recently [38].…”
Section: Genetic Alterations: Copy Number Variations and Mutationsmentioning
confidence: 99%